Same Classroom, Different Reality: Secondary School Students’ Perceptions of STEM Lessons—A Pioneering Study - Lukas Ketscher; Heidrun Stoeger; Wilma Vialle; Albert Ziegler (Education Sciences)
Our study is the first exploration of students’ situational perceptions of STEM lessons based on the DIAMONDS approach. This approach postulates eight perceptual dimensions: Duty, Intellect, Adversity, Mating, pOsitivity, Negativity, Deception, and Sociality. Three research questions were investigated in a validation study involving 447 eighth graders, each based on a distinct validation strategy. (1) Convergent validation strategy: How do students perceive STEM lessons regarding the DIAMONDS dimensions? (2) Criterion-related validation strategy: Are these perceptions associated with STEM education outcomes? (3) Explanatory validation strategy: Do gender differences also appear in the perception of STEM lessons? Data were collected via an online questionnaire. The main results indicated that (1) students associate STEM lessons mainly with Duty and Intellect; (2) their situational perception of STEM lessons was linked to STEM education outcomes; and (3) there were substantial variances in how students perceive STEM lessons. Male students perceived STEM lessons more positively (pOsitivity), while females associated them relatively more with negative attributes (Adversity, Negativity, or Deception). All three validation strategies produced results confirming the validity of the DIAMONDS approach. In this way, the results of our study offer a promising start for the DIAMONDS approach in STEM education research.